2022
DOI: 10.3389/fvets.2022.857634
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Guardian-Relinquishment of Dogs to Shelters: Animal and Regional Predictors in British Columbia, Canada

Abstract: Dogs are relinquished to animal shelters for animal-related or guardian-related reasons. Understanding what drives relinquishment patterns is essential for informing intervention opportunities to keep animals with their guardians. Whereas, overall reasons for relinquishment in a given shelter system have been well explored, analysis of human and animal predictors of relinquishing for a specific reason has not been previously attempted. We used characteristics of relinquishment including year, population of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Behavioral problems in dogs and cats are common and can affect their welfare and quality of life (173), their relationship with humans, and their suitability for assistance work (174). Difficult behavior is frequently cited by owners as being at least one of the reasons for them relinquishing their pets to animal rescue centers, being the primary reason for 10% of dogs in a recent Canadian study (13), and the sole reason for 27% of dogs and 19% of cats in a US study (14). They can also drive some owners to seek elective euthanasia for their pets (15).…”
Section: Behavioral Problems In Dogs and Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral problems in dogs and cats are common and can affect their welfare and quality of life (173), their relationship with humans, and their suitability for assistance work (174). Difficult behavior is frequently cited by owners as being at least one of the reasons for them relinquishing their pets to animal rescue centers, being the primary reason for 10% of dogs in a recent Canadian study (13), and the sole reason for 27% of dogs and 19% of cats in a US study (14). They can also drive some owners to seek elective euthanasia for their pets (15).…”
Section: Behavioral Problems In Dogs and Catsmentioning
confidence: 99%
“…These chronic disorders are common in domestic carnivores, challenging to treat, and have major deleterious effects on health, quality of life and potentially longevity (10)(11)(12). Difficult behavior can lead to a break-down in the humananimal bond, and may result in abuse, relinquishment or euthanasia of pets (13)(14)(15). It is possible that some of the modifiable variables explored may represent ongoing risks that commence or become apparent in early life, and some may be manifestations of DOHaD, with changes in the epigenome at periods of developmental plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The increased risk of relinquishment for pets obtained as a gift is in line often voiced concern from animal charities and organizations that animals given as gifts may end up in shelters (37)(38)(39). However, this finding contrasts with most previous research, where pets given as a gift were not found to be at increased risk of relinquishment (40). For example, Scarlett et al (41) found that only 0.3% of dog owners and 0.4% of cat owners cited "unwanted gift" as a reason for relinquishment across 12 USA animal shelters.…”
Section: Companion Animal Sourcementioning
confidence: 70%
“…Pet owners often under-estimate the financial burden associated with pet ownership (36) and companion animals may compound existing stressors in households in financial difficulty (45). For example, Eagan et al (40) found that 10% of dog owners cited financial reasons as the reason for relinquishment of dogs to a number of Canadian shelters between 2008 and 2019. Similarly, Applebaum et al (4) distributed an online survey to a convenience sample of 3006 USA pet owners, and found that 7% of participants reported concerns and difficulties related to financial problems and caring for their pets during the COVID-19 pandemic.…”
Section: Reasons For Relinquishing a Petmentioning
confidence: 99%
“…25,26 A recent 10-year analysis of BC SPCA surrender reasons found that 83% (n= 55,128/66,694) of feline owner surrenders were for owner-related reasons such as housing and financial challenges. 27 Many owners facing a surrender decision (88% in one study) would prefer to keep their animal if offered support. 28 While preventing shelter intake is the main objective for all animal welfare organizations, focusing veterinary resources on access to care, outreach services and preventative care is likely to have a much greater impact on preserving the human–animal bond within communities than maintaining elective onychectomy.…”
Section: Discussionmentioning
confidence: 99%